Compressive behaviour of a damaged omega stiffened panel: Damage detection and numerical analysis. (1st February 2019) - Sellitto, A.; Riccio, A.; Russo, A.; Zarrelli, M.; Toscano, C.; Lopresto, V.
Abstract: The damage detection of composite material structures is one of the major concerns in aerospace field, given their even more frequent use. In this work, the failure of an aerospace omega stiffened CFRP panel subject to compressive load is experimentally and numerically studied. The specimen is characterised by a 0° oriented notch damage, with respect to the load direction, located in the middle of the bay. A compressive mechanical test has been performed to determine the global buckling phenomenon and the progressive fibre-matrix damage development induced by the compressive load acting on the panel. The panel has been instrumented with back-to-back strain gauges in skin and stringers locations. Non-destructive techniques, such as lock-in thermography and ultrasounds, have been used to detect the damage status. Numerical analyses have been carried out by means of the FE software ABAQUS and the results have been compared against the experimental data. Finally, an un-notched configuration has been numerically tested and the results have been compared against the notched configuration, in order to assess the influence of the pre-existent damage on the mechanical and failure behaviour of the structure during service loading conditions.